The influence of attitude and contextual factor to the ability of entrepreneurship at school of economics Dharma Putra student in Pekanbaru - Adry Nur Perdana; Raden Lestari Ganarsih; Rendra Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was done in School of EconomicsDharma Putraon the Imam Bonjol street No. 75, Pekanbaru. This study aims to determine how to influence attitudes and contextual factorvariables simultaneously and partially on the ability of Entrepreneurship School of Economics Student Dharma Putra Pekanbaru.. Thepopulation in this research werestudent School of Economics Dharma Putra, majoring in Accounting and Management, with a total sample of 74 students. The method of analysis used in this study was descriptive quantitative method of multiple regression using SPSS version 17.00. The results showssimultaneous regression test (F test) that the independent variables studied Attitude and ContextualFactorwere positive and significant impact on the dependent variable (Ability of Entrepreneurship). The magnitude of the effect that the (R²) by twovariables together 70.5% of the dependent variable, while the remaining 29.5% is influenced by other variables not examined in this research. The results of the testing that has been done, the partial regression test (t test) showed that each of the independent variables studied wasattitude has a positive and significant effect on the dependent variable (Ability of Entrepreneurship), whereas the contextual factorvariables have a significant effect on the dependent variable (Ability of Entrepreneurship).Keywords:Attitude, Contextual Factor, Ability ofEntrepreneurship